Pemanfaatan Potensi Lokal Jombang Berupa Bunga Pacar Air Sebagai Indikator Alami - Andri Wahyu Wijayadi; Lina Arifah Fitriyah; Nur Hayati (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Acid base properties can be easily observed based on the difference in color when using indicators. The use of indicators is very rare at the secondary school. Natural indicator are needed to support acid-base learning at the secondary school. This study aims to determine the effectiveness of local potency extract of jombang in the form of henna flowers as a natural indicator and the effectiveness of HVS paper and filter paper as indicator paper. Natural indicator paper was obtained by immersing HVS paper and filter paper in the extract of red and purple henna flowers using water solvent. The test result in acid and base solution  showed that the red and purple henna flower extract had the same effectiveness as a natural indicator, as well the red and purple henna flower extract indicator paper made from HVS paper and filter paper.